Secret agents. - Gilbert, Adrian (London : QED, 2008)
"Discusses American, British, and Russian spies and secret agents, and the history of espionage. Includes profiles of famous spies and double agents"--Provided by publisher.
Includes index.
Keywords: Secret service --Juvenile literature; Spies --Juvenile literature